The Zero-Interest-Rate and the Role of the Exchange Rate for Monetary Policy in Japan - Guenter Coenen; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
In this paper we study the role of the exchange rate in conducting monetary policy in an economy with near-zero nominal interest rates as experienced in Japan since the mid-1990s. Our analysis is based on an estimated model of Japan, the United States and the euro area with rational expectations and nominal rigidities. First, we provide a quantitative analysis of the impact of the zero bound on the effectiveness of interest rate policy in Japan in terms of stabilizing output and inflation. Then we evaluate three concrete proposals that focus on depreciation of the currency as a way to ameliorate the effect of the zero bound and evade a potential liquidity trap. Finally, we investigate the international consequences of these proposals.
urn:nbn:de:hebis:30-10157
Keywords: E31; E52; E58; E61; 330; monetary policy rules; zero interest rate bound; liquidity trap; rational expectations; nominal rigidities; exchange rates; monetary transmission.